2020
DOI: 10.1002/ijgo.13466
|View full text |Cite
|
Sign up to set email alerts
|

Loop electrosurgical excision procedure (LEEP) plus top hat for HIV‐infected women with endocervical intraepithelial neoplasia in Kenya

Abstract: Objective To determine the utility of detecting endocervical cervical intraepithelial neoplasia (CIN) 2+ with endocervical curettage (ECC) and treating with loop electrosurgical excision procedure (LEEP) plus top hat (+TH) among women with HIV. Methods Cytology was followed by coloscopy‐directed biopsy if participants had HSIL or ASC‐H and biopsy plus ECC if there were glandular cells present. CIN2/3 on ECC and/or inadequate colposcopy (ENL) was treated with LEEP+TH, while CIN2/3 on ectocervix (ECL) received L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A study looking at immunosuppressed patients with HIV found no difference in recurrence rates between LEEP-SP and LEEP-TH, suggesting that even in this high-risk population there may be no benefit to the addition of a top hat. 20 Finally, excisional procedures in general only remove cervical tissue and cannot fully remove all HPV-infected cells, which can also impact recurrence risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study looking at immunosuppressed patients with HIV found no difference in recurrence rates between LEEP-SP and LEEP-TH, suggesting that even in this high-risk population there may be no benefit to the addition of a top hat. 20 Finally, excisional procedures in general only remove cervical tissue and cannot fully remove all HPV-infected cells, which can also impact recurrence risk.…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified women who may be at higher risk for undergoing an additional excision, specifically patients who were older, immunosuppressed, had a positive ECS at colposcopy and at time of LEEP, and had an initial HSIL cytology. A study looking at immunosuppressed patients with HIV found no difference in recurrence rates between LEEP-SP and LEEP-TH, suggesting that even in this high-risk population there may be no benefit to the addition of a top hat 20 . Finally, excisional procedures in general only remove cervical tissue and cannot fully remove all HPV-infected cells, which can also impact recurrence risk.…”
Section: Discussionmentioning
confidence: 99%